BILINGUAL VLOG FOR TEACHING MORPHOLOGY - Vera Kristiana (IKIP Siliwangi, 2023)
This study examines the application of a bilingual video blog (VlOG) with content on the process of forming English words in Morphology lectures. Morphology is one of the courses taught in English Literature study program at UMN Al Washliyah, where in the Morphology course students learn about the process of forming words in English. This course is considered difficult by some students because many of the theories taught are related to the process of word formation. During the industrial revolution 4.0 and also during the new normal for the Covid-19 pandemic, it is hoped that the learning process will have several alternatives in its implementation both online and offline. In the lecture process, especially Morphology lectures, learning media is one of the elements that can increase student motivation in learning. Lecturers must be able to utilize technology as an online learning medium so that it does not cause boredom for learning activity. Media applied in Morphology lectures was a bilingual video blog (VLOG) based on the content of the process of forming words in English. A video blog is a blog where there is content in the form of videos in it and will later be uploaded via the social media channel site Youtube. Bilingual video blogs are important for learning courses because they integrate audio-visual in their application so that the material or theory taught by lecturers will be more easily accepted by students both in online and offline lectures. This research is quasi-experimental.Â Keywords:Â Vlog; Word Formation; Morphology